Identification of group A rotavirus gene 4 types by polymerase chain reaction. - Gentsch, J R (1992)
Five genetically distinct human rotavirus (HRV) gene 4 groups have been described on the basis of comparative nucleotide sequencing and the predicted amino acid sequences, and at least four of them represent distinct VP4 antigenic types. To identify each gene 4 type and investigate its distribution in HRV isolates from patients with diarrhea, we developed a polymerase chain reaction (PCR) typing method using sequence information available for four genetically distinct gene 4 types. Rotavirus double-stranded RNAs (dsRNAs) isolated from stool samples were first reverse transcribed and amplified by PCR by using two oligonucleotide primers that correspond to regions that are highly conserved among all known HRV gene 4 types. The 876-bp dsDNA products were then reamplified by PCR in the presence of a cocktail containing one conserved plus-sense primer and four type-specific minus-sense primers (selected from the hypervariable region of gene 4), resulting in products of 345, 483, 267, and 391 bp corresponding to gene 4 types 1, 2, 3, and 4, respectively. This method reliably identified the gene 4 types of 16 well-characterized HRV isolates. Our results were independently confirmed for all 16 strains by reverse transcription and PCR amplification of HRV dsRNA in the presence of alternate type-specific primer pairs. For direct gene 4 typing of HRV in stool samples, we developed a method to extract rotavirus dsRNA from stool specimens by using glass powder. Our results suggest that gene 4 typing will be useful in providing more a complete characterization of HRV strains of epidemiologic or vaccine-related interest.